ANALYSIS OF OIL DUST RELEASED DURING PROCESSING OF METAL SURFACES UNDER LABORATORY CONDITIONS - Xurmamatov, Abdugaffor; Boyturayev, Sarvar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract: Objective. In this article, in the process of metal surface treatment, in order to cover the metal surface, in laboratory conditions, the process of processing metal heated to a high temperature using motor oils is studied. Methods. A laboratory device was used to study this process. Oil-containing gases obtained in laboratory conditions have been studied. Results. The results obtained were compared with the allowable concentration of gases. Absorption cleaning is recommended to retain gases in excess of the permitted rate. The results obtained with the proposed new device were analyzed.